2022
DOI: 10.1186/s12885-022-09943-0
|View full text |Cite
|
Sign up to set email alerts
|

Germline variants profiling of BRCA1 and BRCA2 in Chinese Hakka breast and ovarian cancer patients

Abstract: Objective To investigate the prevalence and spectrum of BRCA1 and BRCA2 mutations in Chinese Hakka patients with breast and ovarian cancer. Methods A total of 1,664 breast or ovarian cancer patients were enrolled for genetic testing at our hospital. Germline mutations of the BRCA gene were analysed by next-generation sequencing, including the coding regions and exon intron boundary regions. Results The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 85 publications
(89 reference statements)
2
5
0
Order By: Relevance
“…The BRCA gene mutation sites are associated with different populations. In the Chinese Hakka population, the most frequent mutation in the BRCA1 gene was c.2635G > T (p.Glu879*), with a frequency of 4/32 (12.5%), which is consistent with previous reports [ 28 ]. This variation involves a single nucleotide alteration in exon 10 of BRCA1 , resulting in an early translation stop signal that leads to nonfunctional protein products.…”
Section: Discussionsupporting
confidence: 90%
“…The BRCA gene mutation sites are associated with different populations. In the Chinese Hakka population, the most frequent mutation in the BRCA1 gene was c.2635G > T (p.Glu879*), with a frequency of 4/32 (12.5%), which is consistent with previous reports [ 28 ]. This variation involves a single nucleotide alteration in exon 10 of BRCA1 , resulting in an early translation stop signal that leads to nonfunctional protein products.…”
Section: Discussionsupporting
confidence: 90%
“…Zhang et al found that the prevalence and spectrum of variants in BRCA1/2 genes in the population which this study was conducted were different from those of other nationalities. 33 BRCA1 and BRCA2 are the tumor suppressor genes, and highly penetrating mutations in these genes result in a loss of tumor suppressor function and thus an increased risk of ovarian cancer. 34 Understanding whether the unique clinical and pathological features of ovarian cancer are associated with the BRCA1/2 gene mutation is essential to mitigate prognosis differences in the female population.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the mutation hotspot in BRCA2 (I770) discovered in our study is the first reported among Chinese patients with gynecological cancer ( 48 50 ). Patients with BRCA2 mutations have a better prognosis than those with BRCA1 mutations ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…reported among Chinese patients with gynecological cancer (48)(49)(50). Patients with BRCA2 mutations have better prognosis than those with BRCA1 mutations (51).…”
Section: B Amentioning
confidence: 98%